OPTIMIZING RESOURCE UTILIZATION: A COMPREHENSIVE APPROACH TO ACCOUNTING IN COMPONENT MANUFACTURING ENTERPRISES - Ali Naser Alwan (Scholar Express Journals, 2024)
Cost management is a essential aspect of enterprise management, influencing the accuracy of cost data calculations, streamlining internal data transfers, and delineating economic responsibilities within cost centers. The choice of cost management methods significantly impacts various facets of a company's operations, both externally and internally. This research paper examines the implementation of resource consumption accounting within component manufacturing enterprises, illustrating its application system through practical examples supported by theoretical research. The study emphasizes the identification and definition of resource accumulation points, operations, cost allocation to auxiliary production departments, and product cost computations. Throughout the system application process, we also scrutinize the disparities between theory and practice, offering insights into addressing practical nuances
Keywords: Resource consumption accounting; Cost management; Applied research